POSITIVE HUMAN RIGHTS OBLIGATION OF STATES AND THE USE OF AUTONOMOUS WEAPON SYSTEMS DURING LAW ENFORCEMENT OPERATIONS - Berkant Akkuş (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Autonomous weapon systems are artificial intelligence-based, modern weapon systems that can identify and destroy targets without meaningful human intervention. In this article, human rights violations that may occur in case of widespread use of autonomous weapon systems in law enforcement operations in the near future will be examined and the positive obligations of states will be determined. States' positive human rights obligations in line with the United Nations, Basic Principles on the Use of Force and Firearms by Law Enforcement Officials, can be listed as weapon selection and the duty of precaution, the official training of law enforcement officers, procedural obligation, the right to explanation and the right not to be subject to completely automatic decisions. The research results of this article offer that, in line with the existing case law of human rights courts, autonomous weapon systems cannot comply with the positive obligation on the right to life.